2017
DOI: 10.3892/ol.2017.6280
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between miR-21 and miR-182 levels in peripheral blood and gastric cancer tissue

Abstract: The relationship between miR-21 and miR-182 gene expression in peripheral blood and gastric cancer tissue was investigated, exploring the relationship between the levels of miR-21 and miR-182 and prognosis of gastric cancer patients, and determining the effects of these two genes on the growth and migration of gastric cancer cells. Fifty gastric cancer patients who were treated in the 254th Hospital of PLA, from July 2012 to July 2014 were selected. Peripheral blood samples were drawn from patients, and 50 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(20 reference statements)
2
5
0
Order By: Relevance
“…We identified that increased levels of both miR-10b, miR-21 and miR-145 significantly were correlated with poor prognosis, miR-10b and miR-21 with DFS and OS, and miR-145 only with OS. Our findings regarding miR-21 are in accordance with the results of Wang et al (14) and Ren et al (19), which showed that the survival times of patients in the group with high miR-21 expression were significantly shorter than those of patients in the groups with normal or low expression. Zhang et al described high expression of miR-21 in GC as being regulated by phosphatase and tensin homolog (PTEN), which is associated with the growth and invasion of GC (20).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We identified that increased levels of both miR-10b, miR-21 and miR-145 significantly were correlated with poor prognosis, miR-10b and miR-21 with DFS and OS, and miR-145 only with OS. Our findings regarding miR-21 are in accordance with the results of Wang et al (14) and Ren et al (19), which showed that the survival times of patients in the group with high miR-21 expression were significantly shorter than those of patients in the groups with normal or low expression. Zhang et al described high expression of miR-21 in GC as being regulated by phosphatase and tensin homolog (PTEN), which is associated with the growth and invasion of GC (20).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the utility of miR-10b, miR-21, miR-93, miR-107, miR-143, and miR-145 as novel diagnostic and prognostic biomarkers of GC was evaluated. Based on previous results and consistently with other studies, statistically significant differences in expression were observed for miR-10b (8,12), miR-21 (7,13,14), miR-93 (9,15), and miR-107 (10,16), enabling the differentiation between tumor and non-tumor control gastric tissue. miR-21 is the most frequently studied oncogenic miRNA in cancer, with overexpression repeatedly confirmed in gastric tumors (7,13,14).…”
Section: Discussionsupporting
confidence: 89%
“…S12, inhibition was specific to miR-21. Levels of mature miR-16 45 (a tumor suppressor miRNA), miR-28 46 (an oncogenic miRNA in intestinal cancers) and miR-182 47 (an oncogenic miRNA, whose expression is closely related to the clinicopathological features of gastric cancer) are not consistently or significantly affected by the compounds in either gastric (AGS) or pancreatic (ASPC1) cell lines, over multiple time scales (24-72 hours), relative to controls where only DMSO was added. In order to assess the molecular mechanism of inhibition of miR-21 expression, we also investigated some of the lower-affinity compounds in the series (44, 46, 50 and 51, Table 1).…”
Section: Pre-mir-21 Binding Compounds Have Specific Cellular Activitymentioning
confidence: 99%
“…Patients usually heal slowly, and even after the burned skin heals, it is transformed into fibrous scar tissue, 1 , 2 accompanied by excessive proliferation of fibroblasts and apoptosis of keratinocytes. 3 , 4 Unfortunately, scars, depigmentation in the affected area, and deformation in the process of skin prognosis are quite common. The inflammatory reaction caused by severe burns can cause further damage to the burned skin tissue and significantly impact the patient's daily life.…”
Section: Introductionmentioning
confidence: 99%